Rapid screening of antioxidant from natural products by AAPH-Incubating HPLC-DAD-HR MS/MS method: A case study of Gardenia jasminoides fruit. (1st February 2023) - Zhuang, Guo-Dong; Gu, Wen-Ting; Xu, Shu-Hong; Cao, Dong-Min; Deng, Si-Min; Chen, Yong-Sheng; Wang, Shu-Mei; Tang, Dan
Graphical abstract: Highlights: AAPH-Incubating HPLC-DAD-HR MS/MS facilitates rapid screening and identification of antioxidants in natural products. AAPH-Incubating HPLC-DAD-HR MS/MS is firstly used for screening antioxidants in Gardenia jasminoides Fruit. Seventeen natural antioxidants were simultaneously identified from Gardenia jasminoides Fruit. Abstract: A new AAPH-Incubating HPLC-DAD-HR MS/MS method was developed for the rapid and high-throughput screening of antioxidants directly in natural products and applied to Gardenia jasminoides fruit. This method was assumed that the peak areas of compounds with potential antioxidant activity in HPLC chromatograms would be significantly reduced or disappeared after incubating with the AAPH which can release ROO at physiological conditions (37 °C, pH 7.4). Additionally, the activity of antioxidants can be evaluated by comparing the peak reduction rates and the screened components can be further identified by HRMS/MS. Then, 17 potential natural antioxidants from the crude extract of GJF was screened. Among them, three major components including crocin I, crocin II and crocetin showed excellent ROO scavenging activity, which were further validated by the ORAC assay. In conclusion, our study provided a simple and effective strategy to rapidly screen antioxidants in natural products.